Hypoglycemic Effect of Ethanol Extract of Snake Fruits Skin (Salacca edulis R.) in Rats (Rattus novergicus) Wistar Induced By Alloxan - Mahulauw, Muhammad Azril Hardiman; Mewar, Djulfikri; Ibrahim, Marisa Anggia; Lihi, Maryam; Tukiman, Suryanti; Fajri, Muh. Danial; Hadijah, Sitti (Jurnal Mandala Pharmacon Indonesia, 2025)
Objective: This study was conducted to determine the effect of reducing blood sugar levels from ethanolic extract of snake fruit peel on male Wistar rats induced by alloxan with fasting blood glucose (FBS) parameters. Method: A total of 30 male Wistar rats were divided into 6 groups (N = 5). Group I (normal control) was not given any treatment. Group II (negative control) was only induced by alloxan 150 mg/kgBW of rats i.p. Group III (positive control) was induced by alloxan 150 mg/kgBW of rats then treated with glibenclamide 0.9 mg/200gBW. Groups IV; V; VI were induced by alloxan 150 mg/kgBW of rats then treated with ethanolic extract of snake fruit peel 2.88 mg/200gBW and 5.76 mg/200gBW; and 11.52 mg/200gBW. Snake fruit peel extract was given from the 4th day to the 27th day. Fasting blood glucose levels were measured on day 0, day 4, day 11, and day 28. Results: The results of qualitative research showed that snake fruit skin contains flavonoid and terpenoid compounds. This study also showed that male Wistar rats experienced a decrease in blood glucose but had not reached normal levels after being given extract doses I, II, and III with each final fasting glucose level of 347.98 mg/dL, 364.68 mg/dL, and 308.18 mg/dL. The final results of the study showed that there was normal fasting blood glucose levels in the positive group while the other groups did not. Conclusion: The dose of 11.52 mg/200gBW when compared to the negative group, doses I and II provided a significant effect of lowering blood glucose but were not yet able to lower blood glucose levels to normal.